1998
DOI: 10.1115/1.2798023
|View full text |Cite
|
Sign up to set email alerts
|

The Penn State Safety Floor: Part II—Reduction of Fall-Related Peak Impact Forces on the Femur

Abstract: The goal of this study was to develop and validate a finite element model (FEM) for use in the design of a flooring system that would provide a stable walking surface during normal locomotion but would also deform elastically under higher loads, such as those resulting from falls. The new flooring system is designed to reduce the peak force on the femoral neck during a lateral fall onto the hip. The new flooring system is passive in nature and exhibits two distinct stiffnesses. During normal activities, the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Our results are in general agreement with previous studies that employed mechanical systems to estimate the effect of compliant flooring on fall impact force, 10,11 although the comparison is made difficult by the fact that previous studies did not report the stiffness of their floor samples. The 8% attenuation we observed in the firm condition is similar to the 7% reduction observed by Gardner et al 11 for a pile carpet and underpad and the 11% reduction observed by Maki and Fernie 12 for 7 mmthick loop carpet.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in general agreement with previous studies that employed mechanical systems to estimate the effect of compliant flooring on fall impact force, 10,11 although the comparison is made difficult by the fact that previous studies did not report the stiffness of their floor samples. The 8% attenuation we observed in the firm condition is similar to the 7% reduction observed by Gardner et al 11 for a pile carpet and underpad and the 11% reduction observed by Maki and Fernie 12 for 7 mmthick loop carpet.…”
Section: Discussionsupporting
confidence: 83%
“…8,9 Second, peak impact forces during simulated falls are reduced between 7 and 23% by compliant floor designs. [10][11][12] However, in the studies providing this evidence falls were simulated with a mechanical test system, which may not accurately measure the force attenuation provided by the floor during falls in humans. Furthermore, data on the stiffness of the tested floor conditions were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thankfully, no injuries to the participant and damage to the fixation occurred indicating that the severity of the forward fall was low. Indeed, the maximum force on impact was approximately four times smaller than the force required for a femoral neck and intertrochantric fractures during sideways fall (40)(41)(42)(43)(44) . Furthermore, the transition between loading and descent phases might present different patterns on each axis depending on the severity and type of fall (e.g., backward, sideways).…”
Section: 5mentioning
confidence: 99%
“…The typical approach relies on simulation of the impact on the fixation using a jig and/or finite element models. [16][17][18][19][20] However, such experiments are only partially realistic since the load applied during a real fall is currently unknown.…”
Section: Need For Better Understanding Of Loads Experiencedmentioning
confidence: 99%
“…Load during a fall of a transfemoral amputeefall. [16][17][18][19][20] Backward falls might create larger bending moments when the prosthetic leg remains tucked under the thigh during the impact.…”
Section: Limitationsmentioning
confidence: 99%